Exploring the Hero’s Journey in Kate Chopin’s The Awakening and Paulo Coelho’s The Alchemist - Bhusal, Damodar (Vox Batauli, 2024)
This research paper explores the quest journeys of the protagonists in Kate Chopin’s The Awakening and Paulo Coelho’s The Alchemist using Joseph Campbell’s concept of the Hero’s Journey from The Hero with a Thousand Faces. The study highlights how the archetypal quest myth is presented in modern narratives. Edna Pontellier in The Awakening embarks on a journey of self-discovery, challenging societal norms and seeking personal freedom. Santiago in The Alchemist follows a more traditional hero’s path, driven by a recurring dream to find a hidden treasure, ultimately realizing that the true treasure lies within. Both journeys lead to significant personal transformations, though their outcomes differ dramatically. While Santiago's journey aligns with the classic structure of departure, initiation, and return, Edna's quest highlights the constraints of her societal context, leading to a tragic conclusion. Santiago encounters physical and spiritual trials in the desert, guided by mentors like Melchizedek and the Alchemist, and returns home enlightened. Conversely, Edna, influenced by characters like Mademoiselle Reisz and Robert Lebrun, faces internal and societal conflicts that ultimately lead her to seek freedom in death. This comparative study illustrates how modern narratives adapt and reinterpret the Hero’s Journey to explore diverse themes and experiences. It emphasizes the enduring relevance of Campbell's monomyth in understanding the complexities of human struggles and aspirations, showing how both protagonists, despite their different paths, reflect universal quests for identity and self-fulfillment. The paper underscores the impact of societal constraints on personal freedom and the varied outcomes of such quests in different cultural contexts.